2017
DOI: 10.1158/1940-6207.capr-16-0281
|View full text |Cite
|
Sign up to set email alerts
|

Loss of BRCA1 in the Cells of Origin of Ovarian Cancer Induces Glycolysis: A Window of Opportunity for Ovarian Cancer Chemoprevention

Abstract: Mutations in the breast cancer susceptibility gene 1 (BRCA1) are associated with an increased risk of developing epithelial ovarian cancer. However, beyond the role of BRCA1 in DNA repair, little is known about other mechanisms by which BRCA1 impairment promotes carcinogenesis. Given that altered metabolism is now recognized as important in the initiation and progression of cancer, we asked whether loss of BRCA1 changes metabolism in the cells of origin of ovarian cancer. The findings show that silencing BRCA1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…BRCA1 is a tumor-suppressor gene and part of the DNA repair complex, which plays an important role in maintaining genomic stability and controlling cell-cycle checkpoints. 56,57 Furthermore, laboratory studies have shown the interaction 58-60 of DNA repair pathways with the inflammation and estrogen pathways through which aspirin mainly operates. 54 Inactivation (silencing) of BRCA1 and PR is thought to occur through gene promoter hypermethylation, 28,55 which appears to affect the efficiency of DNA repair processes, drive dysregulated cell proliferation, and reduce chromosomal stability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BRCA1 is a tumor-suppressor gene and part of the DNA repair complex, which plays an important role in maintaining genomic stability and controlling cell-cycle checkpoints. 56,57 Furthermore, laboratory studies have shown the interaction 58-60 of DNA repair pathways with the inflammation and estrogen pathways through which aspirin mainly operates. 54 Inactivation (silencing) of BRCA1 and PR is thought to occur through gene promoter hypermethylation, 28,55 which appears to affect the efficiency of DNA repair processes, drive dysregulated cell proliferation, and reduce chromosomal stability.…”
Section: Discussionmentioning
confidence: 99%
“…54 Inactivation (silencing) of BRCA1 and PR is thought to occur through gene promoter hypermethylation, 28,55 which appears to affect the efficiency of DNA repair processes, drive dysregulated cell proliferation, and reduce chromosomal stability. 56,57 Furthermore, laboratory studies have shown the interaction [58][59][60] of DNA repair pathways with the inflammation and estrogen pathways through which aspirin mainly operates. Collectively, it is plausible that a tumor environment characterized with BRCA1 and PR promotor methylation may contribute to low sensitivity to aspirin exposure for the host, which would result in little benefit from prediagnosis aspirin use on BC prognosis and overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…BRCA mutations occur in 5-15% of all ovarian cancer cases 49 with significant effects on overall survival 50 and diverse metabolic consequences, such as enhanced glycolysis in ovarian cancer. 51 Cases with BRCA mutations showed overall increased mutational burden harboring higher response rates to immunotherapies, including immune checkpoint blockade. 52 However, comparison of the expression patterns of PD-L1 and PDK1 in cases with mutant and wild-type BRCA in this study revealed no influence of BRCA mutation on PD-L1 or PDK1 levels in ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Among the three types of cancer tested, breast cancer shared same molecular carcinogenesis as ovarian cancer. 7 10 Both the aggressive cancers generally rise from fast-growing epithelial cells through a series of mutation on BRCA1 and BRCA2 genes, inherited mutation of HNPCC gene, and acquired mutation/over-activation of Wnt-β-Catenin signaling. 26 28 Ovarian cancer is often associated with poor survival rate because of being asymptomatic compared to breast tumor, indeed it is resistant to various chemotherapeutic agents, such as cisplatin.…”
Section: Discussionmentioning
confidence: 99%
“… 4 8 The most common type of ovarian cancer is derived from epithelial cells through a series of mutation on tumor suppressor genes (such as PTEN , BRCA1 , BRCA2 , and p53 ), which result from silencing of the genes; 4 6 meanwhile mutation of oncogenes (such as Bcl-2, EFGR, and VEGF) leads to over-activation, thus making the cancer cells autonomous on self-growing and providing resistance to cell death signals or escape from cell cycle checkpoints, ability to invade, and metastasis to distant location which further yields the occurrence of secondary tumor. 9 , 10 As mentioned, ovarian cancer cells are reported with high invasion and metastasis rate, because of high activities from NF-κB gene and subsequent complex formation by several survival and proliferation factors, such as X-linked inhibitor of apoptosis (XIAP) and baculoviral inhibitor of apoptosis repeat-containing gene (BIRC) families (mainly BIRC 1–6). 11 The XIAP formed multiple complexes with respective BIRC; each complex played different function in the development of cancer.…”
Section: Introductionmentioning
confidence: 99%